Effects of a Community-to-Clinic Navigation Intervention on Colorectal Cancer Screening Among Underserved People. Issue 5 (2nd November 2019) - Menon, Usha; Szalacha, Laura A; Kue, Jennifer; Herman, Patricia M; Bucho-Gonzalez, Julie; Lance, Peter; Larkey, Linda
Abstract: Background: Colorectal cancer screening remains suboptimal among poor and underserved people. Purpose: We tested the effectiveness of a community-to-clinic navigator intervention to guide multicultural, underinsured individuals into primary care clinics to complete colorectal cancer screening. Methods: This two-phase behavioral intervention study was conducted in Phoenix, Arizona (2012–2018). Community sites were randomized to group education or group education plus tailored navigation to increase attendance at primary care clinics (Phase I). Individuals who completed a clinic appointment received the tailored navigation in person or via phone (Phase II). Results: In Phase I ( N = 345), 37.9% of the intervention group scheduled a clinic appointment versus 19.4% of the comparison group. In Phase II, 26.5% of the original intervention group were screened versus only 10.4% of the original comparison group. Those in the intervention group were 3.84 times more likely to be screened than were those in the comparison group (odds ratio = 3.84; 95% confidence interval = 1.81–6.92). Conclusions: Translation of an efficacious tailored navigation intervention for colorectal cancer screening to a community-to-clinic context is associated with significantly increased rates of colorectal cancer screening. Navigation assistance to address barriers to screening may serve as the most important component of any educational program to increase individual adherence to colorectal cancer screening. Abstract : Underserved individuals are more likely to get screened for colorectal cancer through a combination of community education and tailored navigation